TATA LAKSANA GIZI HOLISTIK PADA PASIEN PENYAKIT GINJAL KRONIK DENGAN HIPERTENSI RAWAT INAP DI RSU HOLISTIC PURWAKARTA - Yani, Ahmad; Nursoleha, Nela; Zein, Laila Fariha (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: The prevalence of Chronic Kidney Disease (CKD) are getting increase. The etiology of CKD varies greatly with one of the most common cause is hypertension (HT). Nutritional management plays an important role in healing process of patients. The success of nutrition management is determined by the effectiveness of nutritional interventions through diet therapy, education, and counseling that are effective and suitable for patients in the hospital. Objective: This research aims to determine the management of a holistic diet in patients with CKD and HT in the inpatient room of Holistic Hospital Purwakarta. Method: This research is a descriptive study with a case study method. Case subjects were CKD patients with HT and had a history of SLE. Case monitoring was carried out for five days, data collected included primary data, secondary data and data from interviews Results: Diet therapy for CKD patients started from small portions with lowest protein (less than 0.6 g/kgbw/day). The menu consists of natural and organic food ingredients. Food processing uses minimal food process, such as boiled, steamed, and baked, according to the patient's condition. The result showed that the average of food intake with small portion contains 100% nutrition, 161,71% energy, 261,83% protein, 17,30% fat, and 173,62% carbohydrate. The results of laboratory tests of urea is 162 mg/dL, creatinine 6.8 mg/dL, and uric acid 11.9 mg/dL. Patient’s body mass index (BMI) is classified as normal, which is 22.53 kg/m2. The patient's edema condition is reduced, the average fluid intake and discharge are respectively 337 cc/day and 1,146 cc/day. Systolic blood pressure decreases, while diastolic blood pressure increases up to 150/100 mmHg. Conclusion: Holistic nutrition management through nutritional therapy interventions and holistic diet quality of CKD patients with HT and have a history of SLE.